THE ANALYSIS OF STUDENTS’ READING ANXIETY AND THE COPING STRATEGIES IN EFL CONTEXT - Siti Mazidatul Aini (Scientia Integritas Utama, 2022)
The problem that often occurs in reading skills is that when reading text books, students usually feel shy and anxious, afraid to make mistakes while reading, and also slow to read text. So, in this case the present researcher wants to analyze students anxiety in learning English. It is urgent to conduct a descriptive research through the qualitative approach in order to find out the factors that provoke students’ anxiety in reading and to find out the strategies used by the students to overcome their anxiety in reading. The findings of this study revealed that students feel anxious in reading English from two aspects: personal factors and feature texts. These aspects establish that reading in a foreign language also provokes anxiety. The findings also showed that students experienced higher levels of foreign language reading anxiety. The reason for this increase is the increasing level of difficulty in reading the material, both from the personal factor and feature text aspects. These two aspects are represented by five constructs of unknown vocabulary, unfamiliar topic, unfamiliar culture, worry about reading effects, and afraid of making errors. Teachers can help foreign language learners to reduce foreign language reading anxiety by increasing students' confidence to deal with personal factors. As for the students, they need to get involved to reduce anxiety in classroom. Students should respect each other in order to create a friendly environtment. They should help a lower level students when have a difficulty instead of ridiculed them. This would make them feel comfortable with each other. In addition, anxious students should realize that mistakes are a natural part of language learning, therefore, it should not discourage them in learning English.